In silico Exploration of Phospholipase A2 Inhibitor Compounds from Lufariella variabilis as Antivenom of Ophiophagus hannah - Dion, Romario; Ewaldo, Muhammad Farrel; Fauzaan, Muhammad Faishal; Wandi, Ilham Aris; Asih, Rina Sari (Universitas Brawijaya, 2022)
The King Cobra (Ophiophagus hannah) is a venomous snake found in Southeast Asia and South Asia. Globally, it is estimated that there are 81,000 to 138,000 cases of snakebite deaths from 1.8 million to 2 million snakebite cases. The limited availability of antivenom is a problem in handling snake venom poisoning. Exploration of natural ingredients is needed as a preventive measurement from the spread of toxins when they are inside the body. Exploration could be carried out by utilizing natural metabolite compounds that can be inhibitors of the phospholipase A2 (PLA2) enzyme. Luffariella variabilis is known as a marine organism that can produce sesterterpenoid compounds and has the potential as an inhibitor of the phospholipase A2 enzyme. This study aims to explore the potential of sesterterpenoid compounds produced by Luffariella variabilis as an in silico inhibitor of phospholipase A2. Several methods used in this research are molecular docking simulation, toxicity test using pkCSM and Toxtree, and chemical bond analysis using Discovery Studio. The results showed that the manoalide compound was the most potent compound of the other sesterterpenoid compounds in its ability to become a snake antivenom candidate.